Dualizm bytu i powinności w czystej teorii prawa Hansa Kelsena - Huk, Marta Z. (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
Following paper is concerned with the problem of Is/Ought dichotomy in Hans Kelsen’s Pure Theory of Law. This is one of the most important problems which needs to be addressed in order to provide autonomous legitimacy of law in terms of normativism. The claim that those two spheres ought to be separated, is analysed from three different philosophical perspectives: ontological, epistemological and normative. Each of them posits Kelsen’s dichotomy as essential to a development of his concepts. The paper is an attempt to answer the question why this distinction is necessary in the context of legal validity and effectiveness.